Integrated Clinical Scale Manufacturing System for Cellular Products Derived by Magnetic Cell Separation, Centrifugation and Cell Culture. Issue 1 (25th January 2013) - Apel, Michael; Brüning, Mareke; Granzin, Markus; Essl, Mike; Stuth, Juliane; Blaschke, Jessica; Spiegel, Iris; Müller, Sabine; Kabaha, Eiad; Fahrendorff, Elmar; Miltenyi, Stefan; Schmitz, Jürgen; et al.
Abstract Manufacturing of cellular products for therapeutic purposes like stem cell or cancer therapy requires equipment with specific characteristics not always addressed by conventional technologies. A new integrated cell processing device is presented that can handle all current technical requirements for manufacturing cellular products by automation of the complete process in a GMP‐compliant single‐use tubing set. Its capabilities are exemplified in the presented study by successful processing of adult stem cells, natural killer cells, and several cell lines. Multiple cell processing workflows can be automated in a functionally closed environment: from cell separation through cell culture to formulation of the final product.